Optimally Enhancement Rural Development Support Using Hybrid Multy Object Optimization (MOO) and Clustering Methodologies: A Case South Sulawesi-Indonesia - Faisal, Muhammad; T.K.A, Rahman (2023)
This research aims to propose a strategy for equitable development by gathering information on the living conditions of people in rural areas and grouping villages based on the Community Standard of Living Index (CSLI). Rural areas often face issues such as poverty, inequality, and inadequate access to services, necessitating a rural development strategy for poverty alleviation and empowerment of rural communities. The foundation of successful survey based research is accurately describing the practices, conditions, experiences, personal characteristics, or opinions of respondents through the questions asked. The stages of this study include the validation of 38 criteria by experts, verification and evaluation using the MOO-Fuzzy Delphi method, weighting with the RR method, village scoring, and clustering using the SOM method. The scores from all respondents were calculated and used as input for the scoring process, which determined the village score. The results indicate that 10 villages fall into the Poor Level of CSLI group. The innovation of this study lies in the method used to develop the Community Standard of Living Index for each village, providing a potential solution for addressing the lack of community participation and delays in presenting information about development conditions in villages.